2014
DOI: 10.1074/jbc.m113.532846
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Stimulation of Cytochrome P450 46A1 and Cerebral Cholesterol Turnover in Mice

Abstract: Background: Elevation of cerebral cholesterol turnover in mice due to increased CYP46A1 expression has palliative effects on hallmarks of Alzheimer disease. Results: CYP46A1 could also be activated post-translationally by drugs in vitro and in vivo. Conclusion: CYP46A1 is a viable therapeutic target. Significance: Pharmacologic stimulation of CYP46A1 and cerebral cholesterol turnover may lead to new therapeutic strategies for the treatment of brain disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
117
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(120 citation statements)
references
References 48 publications
3
117
0
Order By: Relevance
“…The fragment at m/z 413 confi rmed the product to be 25-hydroxy-7-dehydrocholesterol. been shown in a mouse model ( 53 ). We have not examined the effects of any of these drugs on the new reactions we characterized here.…”
Section: Discussionmentioning
confidence: 99%
“…The fragment at m/z 413 confi rmed the product to be 25-hydroxy-7-dehydrocholesterol. been shown in a mouse model ( 53 ). We have not examined the effects of any of these drugs on the new reactions we characterized here.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in vitro and in vivo revealed that CYP46A1 can bind compounds other than cholesterol, including sterols and some marketed drugs (6 -13), with compound binding leading to enzyme inhibition (8,10). Unexpectedly, several inhibitory pharmaceuticals were also found to act, at specific concentrations, as enzyme activators enhancing CYP46A1-mediated 24HC production (7,13). Both increase and decrease of CYP46A1 activity have therapeutic potential (14); therefore, we began to ascertain the molecular basis of CYP46A1-drug interactions.…”
Section: Cytochrome P450 46a1 (Cyp46a1)mentioning
confidence: 99%
“…In contrast, binding of the activating drugs is not yet fully understood but began to be elucidated for efavirenz (EFV), a Food and Drug Administration-approved anti-HIV medication. We established that, both in vitro and in vivo (in mice), the dependence of CYP46A1 activity on EFV concentration represents a bell-shaped curve with CYP46A1 activation at low EFV concentrations and inhibition at higher drug concentrations (13). We also generated a model of CYP46A1 activation by EFV (13) according to which CYP46A1 has two separate sites: the allosteric site located on the cytosolic surface of the molecule and the active site embedded in the lipid bilayer.…”
Section: Cytochrome P450 46a1 (Cyp46a1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the large quantity of hits to be tested and the limitation of LC-MS capacity, the test was separated into nine individual experiments with eight repeats of each control in each experiment. A total of 35 DNPEP inhibitors was confirmed by the first orthogonal screen, whereas no activators were active in this assay, which is not surprising given the inherent general difficulty in finding compounds that stimulate enzyme activity (Bishop and Chen, 2009;Mast et al, 2014) (Supplemental Tables 7 and 8). The low enrichment of hits confirmed from the orthogonal screen can be attributed to two main factors.…”
mentioning
confidence: 98%